2021
DOI: 10.3390/ijerph18189859
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Pollution Exposure of Women in Adama, Ethiopia, and Assessment of Disease Burden Attributable to Risk Factor

Abstract: Introduction and aim: Air pollution, a major environmental threat to human health, contributes to the premature deaths of millions of people worldwide. Cooking with solid fuels, such as charcoal and wood, in low- and middle-income countries generates very high emissions of particulate matter within and near the household as a result of their inefficient combustion. Women are especially exposed, as they often perform the cooking. The purpose of this study was to assess the burden of disease attributable to hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…A systematic review from 2020 found positive associations between wood smoke and increased blood pressure, low birth weight, esophageal cancer, sick building syndrome, non‐syndromic cleft lip and/or cleft palate, and under‐five mortality. That indoor air pollution from solid biomass fuels is a strong risk factor for hypertension was also shown by, for example, Li et al 18 A recent health impact assessment study 19 estimated the burden of disease of acute lower respiratory infections, chronic obstructive pulmonary disease, ischemic heart disease, lung cancer, and stroke in an Ethiopian cohort of 2000 women and concluded that the disability‐adjusted life‐years (DALYs) lost per 100 000 women ranged between 6000 and 9000, per disease.…”
Section: Introductionmentioning
confidence: 67%
“…A systematic review from 2020 found positive associations between wood smoke and increased blood pressure, low birth weight, esophageal cancer, sick building syndrome, non‐syndromic cleft lip and/or cleft palate, and under‐five mortality. That indoor air pollution from solid biomass fuels is a strong risk factor for hypertension was also shown by, for example, Li et al 18 A recent health impact assessment study 19 estimated the burden of disease of acute lower respiratory infections, chronic obstructive pulmonary disease, ischemic heart disease, lung cancer, and stroke in an Ethiopian cohort of 2000 women and concluded that the disability‐adjusted life‐years (DALYs) lost per 100 000 women ranged between 6000 and 9000, per disease.…”
Section: Introductionmentioning
confidence: 67%
“…IAP is a less studied subject in Ethiopia, and synthesizing available evidence in the literature is very challenging owing to the evidence quality and heterogeneity. Several studies have found a link between biomass fuel use and acute respiratory infections, asthma, chronic obstructive pulmonary disease, and tuberculosis in Ethiopian households ( Andarge et al., 2021 ; Balidemaj et al., 2021 ; Desalegn et al., 2011 ; Downward et al., 2018 ; Mengesha et al., 2004 ; Tamire et al., 2020 ; Andualem et al., 2020 ). According to a study conducted in Gondor, the prevalence of respiratory symptoms among women was 46.1% [95% CI: 42.6 %–49.7 %], with a runny nose, shortness of breath, and phlegm accounting for 32.07 %, 15.03 %, and 12.63 %, respectively ( Andualem et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, larger households often consume a high volume of biomass fuel for domestic purposes, such as cooking, heating and lighting, which would increase the concentration of harmful particulate matter in the indoor environment 31 32. Previous studies from Ethiopia have revealed that using firewood for cooking was responsible for about half of acute lower-respiratory tract infections and deaths from lung cancer 33. In this study, the odds of dying from respiratory-related diseases were observed to be higher among households that used wood and/or animal dung for cooking purposes.…”
Section: Discussionmentioning
confidence: 99%